P14 The impact of audit on CNS team development. (1st October 2013) - Gibson, Vanessa; Patel, June
Abstract : In 2011 the Hospice Clinical Nurse Specialist (CNS) team were facing a significant increase in patient referrals numbers (approximately 70 per month). The demand for community based care, rather than acute hospital admission, was also resulting in increasingly complex and urgent referrals from all areas of the local healthcare economy. In addition, palliative and end-of-life care services traditionally available only to cancer patients were increasingly being accessed by patients with non- malignant diagnoses. In response the CNS team undertook a month long audit of referrals to the community nurse specialist service. The audit revealed: Low levels of referral information, resulting in delayed contact Difficulties assessing levels of urgency Lack of clarity regarding other services involved with the patient Unnecessary home visits As a result the CNS team has now introduced the following: A new streamlined referral process A full time specialist triage nurse who makes first contact with all referrals: She: Responds to all referral agencies Assesses level of urgency Holds her own low-level caseload that she contacts by phone Helpline established and available to patients and health care professionals: this service provides immediate access to a highly skilled CNS Accessing and completing the electronic notes systems to ensure comprehensive and up to date clinical information is readily available to the wider healthcare team. Enhanced patient documentation Continuous development is key and plans are being developed for: A visiting 'rapid response' CNS A nurse led triage clinic Increased triage nurse hours The CNS team have used audit to truly 'hear' what is happening in practice and as a result have used this knowledge to lead service redesign- a key aspect of the CNS role identified by National Cancer Action Team (2010)